Kepercayaan dan Hegemoni dalam Cerpen “Makelar” Karya Sri Lima R.N. (Kajian Hegemoni Gramsci) - Fajrul Falah (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
This study aims to express the trust and hegemony in the "Broker" short story by Sri Lima R.N. This research is motivated by the idea that language in fiction or short stories is meaningful and indicated not to be neutral.  The language in the short story, became the media for sending message content to the author as a reflection of the social community referred to. The approach used in this study is the sociology of literature, specific to the study of Gramsci hegemony. The research method used is descriptive qualitative.  Research data obtained from text, words, phrases, sentences, contained in short stories related to trust and hegemony. The research data is then described and expressed based on the approach used. The results of the study show that there was a change in the characteristics of Handoko's character as a broker who was initially good, become opportunist. Brokerage profession is used as a tool to hegemony the public to get profits. Community trust in brokers and people who are considered smart also grow. However, Handoko's figure was eventually protested by people who had used their services and failed. Handoko or brokers run away from the protests and demands of the people.